Optimizing the adhesion of soil-touching parts based on biomimetic concepts using the Taguchi method - Salem, Abouelnadar El.; Zhang, Guozhong; Abdeen, Mohamed Anwer Mahmoud; Wang, Hongchang; Gao, Yuan (International Journal of Agricultural and Biological Engineering, 2022)
Several studies highlighted that the surface shape modifications which are inspired by the soil-burrowing animals have positively impacted the soil-tool adhesion; however, it is still unclear what the optimum dimensions of the domed surface are for minimizing soil-tool adhesion. In this study, twenty-seven domed discs were created according to Taguchi orthogonal array L27(33) to determine the optimum dimensions of the domed surface that minimize normal adhesion force and disc sinkage simultaneously, as well as comparing the effect of the optimized domed disc versus the flat disc on the normal adhesion force under different soil conditions. The results revealed that disc coverage ratio and dome height to diameter ratio are essential to design parameters that influence the normal adhesion force of discs. According to the signal-to-noise ratio analysis, it was observed that the combination of 60% disc coverage ratio, 25% dome height to diameter ratio, and 10 mm dome base diameter was found to be the most appropriate for the well-balanced improvement of both normal adhesion force and disc sinkage simultaneously. In all treatments, the optimized domed disc produced less normal adhesion force than the flat disc (about 7%-18%, according to soil condition). It can be concluded that properly designed domed surfaces can significantly reduce the normal adhesion force when compared to flat surfaces.Keywords: biomimetics, paddy soil, normal adhesion, disc sinkage, Taguchi methodDOI: 10.25165/j.ijabe.20221501.6147Citation: Salem A E, Zhang G Z, Abdeen M A M, Wang H C, Gao Y. Optimizing the adhesion of soil-touching parts based on biomimetic concepts using the Taguchi method. Int J Agric & Biol Eng, 2022; 15(1): 147–154.